Arduino Uno-Based Tool Temperature Control Design Using A Cooling System In The Turning Process - Ezra Kurniawan Ezra Kurniawan; Razali (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The turning process generates heat due to the arrangement between the tool and the workpiece which can increase the temperature of the tool thereby accelerating tool wear and reducing the quality of machining results. This research aims to design an Arduino Uno-based tool temperature control system using a cooling system and determine its effectiveness in reducing the temperature of the tool in the turning process. The research method used was an experimental method by measuring test results without a cooling system and with a cooling system at a variation of feed rates of 0.10 mm/rev, 0.15 mm/rev, and 0.20 mm/rev as well as cutting depths of 0.4 mm, 0.8 mm, and 1.2 mm. Temperature data were analyzed using a comparative descriptive analysis method. The results showed that the average temperature without a cooling system was 41.79°C, 45.48°C, and 50.92°C, respectively, while with a cooling system it was 39.91°C, 40.02°C, and 41.28°C. The percentage of temperature reduction obtained was 4.50%, 12.01%, and 18.93%. These results show that the Arduino Uno-based cooling system is able to effectively control the chisel temperature, especially in cutting conditions with higher feed rates. Thus, the system designed can maintain a more stable tool temperature so that it has the potential to increase the life of the tool and the quality of the turning.